PENCEGAHAN STUNTING MELALUI PAGI SENIN (ASUPAN GIZI SEIMBANG DAN IMUNISASI RUTIN) - Khumairoh; Nindia Putri, Anisa; Khaira Ayuning Putri, Serzia; Husni, Abi; Taofik, Herlan; Arnetta Putri, Mela; Widiawati, Windi; Muharry, Andy (Jurnal Pengabdian Masyarakat Indonesia, 2023)
Nutritional problems are a global issue that affects regions around the world and has a profound impact on the quality of human resources. One of the primary global nutritional challenges is stunting. Cipicung Village is situated in a designated area with a high prevalence of stunting cases. The results of a home visit validation survey conducted by the Culamega Community Health Center revealed that Cipicung Village had the highest number of stunting cases, with 63 children under the age of five. The goal of this community service activity is to encourage community participation in efforts to prevent stunting. This is achieved by promoting regular visits to the posyandu, maintaining a balanced nutritional diet, and emphasizing the importance of implementing Clean and Healthy Living Behavior (PHBS). The activity employs a lecture-based approach followed by a question and answer session, involving PKK mothers, posyandu cadres, and the general public, particularly those with toddlers. This activity was conducted on July 9, 2023, and was attended by 53 participants. Through the implementation of this educational activity, there has been a significant increase in the audience's knowledge, as evidenced by the pretest-posttest results with a p-value of 0.000. This educational initiative has been successful in enhancing the community's awareness and knowledge after its completion.